Cost-benefit of implementing a vaccination and deworming program in dual-purpose production units in Veracruz tropics (Agro Productividad, 2025)
Objective: To evaluate the cost-benefit of implementing a Vaccination and Deworming Program (PdVyD) in commercial farms in the central region of Veracruz, Mexico.Design/Methodology/Approach: Based on a survey, information on livestock health problems and practices was collected from eight farms located in six municipalities in this region.Results: No farmer has an adequate program for controlling livestock diseases, so it would be useful to rely on a PdVyD. Cattle deaths were recorded in all farms. Average cost per head in Mexican pesos (MXN/head) of medicines was grouped in four groups: A) Vaccines for reproductive diseases, $49.85; B) Bovine rabies vaccine, $22.27; C) Clostridiasis vaccines, $22.63; and D) Dewormers, $21.22. The total cost of a PdVyD for a medium size farm (70 head) was $8,655 a year; in this, the Vaccination Program (PV, groups A, B, and C) accounts for $6,633 (76.6%) a year, and the Deworming Program (PD) (group D) for $2,022 (23.4%) a year. For a small size farm (25 head), the total cost of PdVyD was $3,128 a year, broken down into $2369 (75.7%) for PV, and $759 (24.3%) for PD.Study Limitations/Implications: The analysis is focused on the last year of operations and only considers eight production units.Findings/Conclusions: Practices for preventing diseases among the participants lacks regularity. The cost of a PdVyD is lower than livestock losses, even without considering losses in productive efficiency due to diseases. The implementation of a PdVyD requires to improve farms managementand promotion among producers by the technicians.